اعتبار القدرة في التكليف وتطبيقاته الأصولية في مسائل الحكم التكليفي - العرابي، فهد بن عبيد بن عبدالله (جامعة الأزهر - كلية الدراسات الإسلامية والعربية للبنات بكفر الشيخ, 2019)
بحث بعنوان اعتبار القدرة في التكليف، ويهدف إلى بيان قاعدة لنبني عليها جملة من التطبيقات الأصولية، عن طريق بناء الأصول على الأصول، وبيان مدى ترابط علوم الشريعة، فمسائل البحث مبنية على مسائل علم العقيدة، واتبعت أسلوب التتبع والاستقراء، والتحليل لكلام الأصوليين، مع بيان وجه ابتنائه على القاعدة مدار البحث، وتضمن مقدمة وفصلين، فصل في الجانب النظري في تعريف التكليف والقدرة، وأنواع القدرة وأسباب انتفائها، وخلاف العلماء في ذلك، وفصل في التطبيقات الأصولية وهي: الواجب المخير، والمحرم المخير، وما لا يتم الواجب إلا به، وتوقيت العبادة بوقت لا يسعها بتمامها، وخلصت إلى أن علم بناء الأصول على الأصول من العلوم التي تجلى علم أصول الفقه وقواعده؛ إذ به يعرف مآخذ الأصوليين فيما ذهبوا إليه، وأن خلافهم في مسائل العقيدة له أثر لا يمكن إنكاره في مباحث وقواعد علم أصول الفقه، وأوصي إخواني من طلبة العلم في استكمال بقية المباحث، لمعرفة الأصول التي بنيت عليها القواعد الأصولية.
A research, which is entitled the importance of capacity in divine commands, aims to demonstrate the rule on which a set of fundamentalist applications are established by analogizing the fundamentals over the fundamentals, and indicating the coherence of Sharia’ science (Islamic science). The research theses are based on the matters of theology, following the method of extrapolation and induction, and analyzing the sayings of fundamentalists with an explanation how the rule of research is established. The research includes a preface and two chapters. The first chapter demonstrates the theoretical aspect of the definition of divine commands and capacity, the types of capacity and the reasons for its absence with explaining the disagreement of scholars relating to this. The other chapter demonstrates the fundamentalist applications, namely: the optional obligatory, the optional forbidden, what is not done but with an obligation, and the restricted obligatory. It is concluded that the science of analogizing the fundamentals over the fundamentals is one of the sciences that reveals the fundamentals of jurisprudence science and its rules, as it defines the agreements of fundamentalists, and that their disagreement in matters of theology has an undeniable effect in the topics and rules of the fundamentals of jurisprudence science. I recommend my fellow scholars to complete the remaining of the research objects in order to know the fundamentals on which the fundamentalist rules were established.
Keywords: التكليف -- الحكم التكليفى -- الفقه الإسلامى -- القواعد الفقهية -- الشريعة الإسلامية